MODALITAS INCUMBENT INDAH DHAMAYANTI PUTRI PADA PEMILIHAN KEPALA DAERAH DI KABUPATEN BIMA TAHUN 2020 (Jurnal Nawala Politika, 2023)
This study aims to find out how the ownership and distribution of capital is so that Incumbent Indah Dhamayanti Putri can win again in the regional head elections in the Bima district in 2020. In looking at the ownership and distribution of capital the researcher uses the theory of capital by Pierre Bourdieu which explains that there are three four capitals, namely capital social capital, economic capital, political capital and symbolic capital. In this study using the literature review research method with the aim of discussing literature related to or related to certain topics. The findings are as follows: First, the social capital owned is in the form of hereditary factors from the Bima sultanate. Second, his political capital, when he was chairman of the Bima Regency DPRD from the Golkar party. Third, the economic capital from LHKPN data is 14.8 billion Rupiah. Fourth, its symbolic capital as part of the Bima sultanate so that it is close and familiar to the people as well as acceptance from the Bima people. Keywords: Incumbent, local elections, capital